Bi / UiO-66 binary composite photocatalytic material as well as preparation method and application thereof

By preparing Bi/UiO-66 binary composite photocatalytic materials, combined with the advantages of UiO-66 and BiOI, the shortcomings of BiOI in pollutant degradation effect in the prior art are solved, and efficient adsorption and photocatalytic degradation of antibiotics in water bodies are achieved.

CN119771502APending Publication Date: 2025-04-08泰州学院
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411810589.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has not yet discovered a method of combining BiOI with MOF materials to adsorb organic pollutants in water, resulting in insufficient pollutant degradation effect of BiOI.

Method used

Bi/UiO-66 binary composite photocatalytic material was prepared by in-situ reduction synthesis method, combining the structural stability of UiO-66 and the photocatalytic performance of BiOI to achieve efficient adsorption and photocatalytic degradation of pollutants.

Benefits of technology

It realizes efficient adsorption and degradation of antibiotics in water, has ideal adsorption and photocatalytic synergistic effects, high photocatalytic efficiency, and simple preparation method, green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771502A_ABST
    Figure CN119771502A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of photocatalyst materials, and particularly relates to a Bi / UiO-66 binary composite photocatalytic material as well as a preparation method and application thereof. According to the preparation method, the advantages of BiOI and UIO-66 are ingeniously combined, and UIO-66 serving as a metal organic framework with a stable structure has a richer and adjustable aperture structure and an oversized specific surface area, so that adsorption and enrichment of pollutants are facilitated. The Bi-coated UiO-66 photocatalytic material taking the UiO-66 as the carrier disclosed by the invention has an ideal synergistic effect of adsorption and photocatalysis, and has very good catalytic activity. The Bi / UiO-66 composite catalyst is prepared through an in-situ reduction synthesis method, and the preparation method is simple, green, environmentally friendly, free of secondary pollution and high in photocatalytic efficiency and has certain commercial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalyst material preparation, and specifically relates to a Bi / UiO-66 binary composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] Photocatalysis can remove harmful pollutants under mild operating conditions and is considered to be an economical, efficient and green treatment technology with practical application value, thus attracting widespread attention from researchers.

[0003] Metal-organic framework (MOF) is a porous material with a three-dimensional periodic network structure formed by the orderly arrangement of organic ligands and metal centers. Due to the advantages of a wide variety of metal nodes and organic ligands that make up MOFs, diverse structures, and easy chemical modification and functionalization, it has broad application prospects in many research fields such as gas storage, separation, catalysis, and sensing. The UiO-66 (UiO = University of Oslo) series of organic metal framework materials are metal organic framework materials with Zr as the metal center and 1,4-terephthalic acid (H2BDC) and its derivatives as organic ligands. UiO-66 is a complex of regular octahedral Zr6O4(OH)4 metal clusters and H2BDC. Its structure contains two types of octahedral and regular tetrahedral pore cages, which are connected to each other through triangular pore windows. Compared with other MOFs materials, UiO-66 has excellent stability and strong acid and alkali resistance. It is a unique MOF material.

[0004] BiOI is a type of LBB (layered bismuth-based) photocatalyst. 6s Orbital and O 2p Orbital hybridization forms a wider hybrid state, which not only leads to a narrow band gap and enhanced light absorption, but also leads to a highly dispersive band structure with fast charge migration. A single layer of BiOI consists of a [Bi2O2] 2+ and two I - The layers are connected by strong covalent bonds and the interlayers are connected by weak van der Waals forces, forming a stacked layer pattern of [I-Bi-O-Bi-I], which provides the driving force for the separation of electrons and holes. In terms of energy band structure, BiOI is an indirect band gap semiconductor. 6p orbitals make up the bottom of its conduction band, O 2p and I 5pThe orbitals form the top of its valence band. Since the bottom of the conduction band and the top of the valence band of the indirect bandgap semiconductor do not belong to the same K point in the K space, the photogenerated electrons on BiOI need to first cross the K space horizontally to jump back to the conduction band, further reducing the possibility of recombination of photogenerated electrons and photogenerated holes. BiOI's unique layered structure and the characteristics of indirect bandgap semiconductors make BiOI exhibit good photocatalytic effects. However, its valence band position is not positive enough, the oxidation ability of photogenerated holes or hydroxyl radicals is relatively weak, and the degradation effect on pollutants is weakened. So far, no reports have been found on the combination of BiOI and MOF materials to adsorb organic pollutants in water. Summary of the invention

[0005] In view of this, in order to solve the deficiencies in the prior art, the present invention provides a Bi / UiO-66 binary composite photocatalytic material and its preparation method and application. The Bi / UiO-66 binary composite photocatalytic material of the present invention has a highly efficient photocatalytic degradation effect on pollutants and can achieve highly efficient adsorption and degradation of antibiotics in water.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a Bi / UiO-66 binary composite photocatalytic material, and the preparation method thereof is as follows: (1) Dissolve Bi(NO3)3·5H2O and KI in ethylene glycol, transfer to a stainless steel reactor lined with polytetrafluoroethylene after ultrasonic stirring, and cool the solution to room temperature after high temperature reaction, wash and dry to obtain BiOI; (2) ZrCl4, the organic ligand, and the BiOI prepared in step (1) are dissolved in a DMF solution and stirred evenly, a regulator is added, and ultrasonic stirring is performed to obtain a homogeneous suspension; the homogeneous suspension is transferred to a stainless steel reactor lined with polytetrafluoroethylene, reacted at high temperature, cooled to room temperature, washed, and dried to obtain a Bi / UiO-66 composite material.

[0007] In step (1), the dosage ratio of Bi(NO3)3·5H2O, KI and ethylene glycol is 5mmoL:5mmoL:40mL.

[0008] The temperature of the high temperature reaction in step (1) is 150°C-170°C, and the time of the high temperature reaction is 10 h-12 h.

[0009] The mass ratio of Bi to UIO-66 in the Bi / UiO-66 composite material in step (2) is 0.1-0.5:1.

[0010] The dosage ratio of ZrCl4, organic ligand, BiOI and DMF in step (2) is 1 mmoL: 1 mmoL: 0.0467-0.2335 g: 50 mL.

[0011] The molar ratio of the organic ligand to the regulator in step (2) is 1:1; The regulator in step (2) is selected from formic acid, acetic acid, trifluoroacetic acid, HCl, HF, and water.

[0012] The organic ligand described in step (2) is selected from terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-bromoterephthalic acid, 2-nitroterephthalic acid, 1,2,4-benzenetricarboxylic acid, 2,5-diaminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dimercaptoterephthalic acid or 2,3,4,6-tetrafluoroterephthalic acid.

[0013] The temperature of the high temperature reaction in step (2) is 100-140° C., and the time of the high temperature reaction is 12-30 hours.

[0014] The present invention also provides a Bi / UiO-66 composite material prepared according to the preparation method as described above.

[0015] The present invention also provides an application of the Bi / UiO-66 composite material as described above in the field of antibiotic adsorption in water bodies.

[0016] Preferably, the antibiotic is one or more of quinolone antibiotics and tetracycline antibiotics.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention cleverly combines the advantages of BiOI and UIO-66. UiO-66, as a metal organic framework with a stable structure, has a richer and adjustable pore structure and a large specific surface area, which is conducive to the adsorption and enrichment of pollutants. The Bi@UiO-66 photocatalytic material with UiO-66 as a carrier of the present invention has an ideal synergistic effect of adsorption and photocatalysis, and has good catalytic activity. The present invention prepares the Bi / UiO-66 composite catalyst by an in-situ reduction synthesis method, the preparation method is simple, green and environmentally friendly without secondary pollution, high photocatalytic efficiency, and has certain commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the XRD pattern of different substances; Figure 2 is a graph showing the photocatalytic degradation of norfloxacin by BiOI monomer and different Bi / UiO-66 composite materials prepared in Example 1; Figure 3 It is the ultraviolet diffuse reflection graph of UiO-66 monomer and the series of Bi / UiO-66 composite materials prepared in Example 1; Figure 4This is the active capture photocatalytic degradation diagram of Bi / UIO-66=0.1:1; Figure 5 It is the degradation diagram of Bi / UIO-66=0.1:1 with different ion concentrations; in the figure, (a) is the degradation curve, and (b) is the degradation rate; Figure 6 This is the cyclic degradation diagram of norfloxacin with Bi / UIO-66=0.1:1; Figure 7 This is the photocatalytic degradation diagram of Bi / UIO-66=0.1:1 with different mass concentrations; (a) is the degradation curve and (b) is the degradation rate. DETAILED DESCRIPTION

[0019] In order to more fully understand the technical contents of the present invention, the technical solutions of the present invention are further described and introduced below in conjunction with specific examples. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The preparation method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0020] It is clear to those skilled in the art that, hereinafter, unless otherwise specified, the materials and operating methods used in the present invention are well known in the art, the experimental methods used are conventional methods, and the materials and reagents used can be purchased from chemical reagent companies. The UiO-66 described in the present invention can also be prepared by the following preparation method: Preparation of UiO-66: 0.2330 g ZrCl4 and 0.1661 g terephthalic acid were dissolved in 50 mL DMF solution, and 3.6 mL acetic acid was added, and ultrasonic stirring was performed for 30 min to obtain a homogeneous suspension A; the homogeneous suspension A was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel reactor, and reacted at 120 ° C for 24 h. The solution was cooled to room temperature and washed with ethanol and deionized water for 3 times. After drying at 80 ° C for 12 h, an off-white powder was obtained, which is UiO-66.

[0021] Example 1: Preparation of Bi / UiO-66 composite material (1) Dissolve 2.43 g Bi(NO3)3·5H2O and 0.83 g KI in 40 mL ethylene glycol and stir ultrasonically to obtain a homogeneous suspension B. Transfer the homogeneous suspension B to a 100 mL polytetrafluoroethylene-lined stainless steel reactor and react at 160°C for 12 h. Cool the solution to room temperature and wash it with ethanol and deionized water three times. After drying at 80°C for 12 h, an orange-yellow powder is obtained, which is BiOI.

[0022] (2) Dissolve 0.2330 g ZrCl4, 0.1661 g terephthalic acid, and 0.0466 g BiOI prepared in step (1) in 50 mL N,N-dimethylformamide (DMF) solution and stir, then add 3.6 mL acetic acid and stir ultrasonically to obtain a homogeneous suspension C; transfer the homogeneous suspension C to a 100 mL polytetrafluoroethylene-lined stainless steel reactor and react at 120°C for 24 h. Cool the solution to room temperature, wash it with ethanol and deionized water three times, and dry it at 80°C for 12 h to obtain an off-white powder, which is a Bi / UiO-66 composite material, denoted as Bi / UiO-66=0.1:1.

[0023] Referring to the preparation method of Example 1, the addition amount of BiOI was adjusted to 0.0934 g, 0.1401 g, 0.1832 g, and 0.2335 g, respectively, to prepare Bi / UiO-66 composite materials with different Bi source contents, and the products were recorded according to different mass ratios as: Bi / UiO-66=0.2:1, Bi / UiO-66=0.3:1, Bi / UiO-66=0.4:1, and Bi / UiO-66=0.5:1.

[0024] Example 2: Structural Characterization The crystal forms of the samples were detected by using an XD3 polycrystalline X-ray diffractometer within 5° to 80°, and the structures of BiOI, UiO-66 and different Bi@UiO-66 prepared in Example 1 were identified respectively. Figure 1 is the XRD pattern of different substances; Figure 1As shown, the diffraction peaks at 2θ positions of 7.4°, 8.5°, 12.1°, 14.8°, 17.1° and 30.8° correspond to the (111), (200), (222), (400), (442) and (711) crystal planes of UIO-66, respectively; the diffraction peaks at 2θ positions of 29.7°, 31.8°, 45.5° and 55.3° correspond to the (012), (110), (020) and (122) crystal planes of BiOI, respectively. The XRD theoretical and actual spectra of monomer BiOI and UiO-66 are in good agreement and have high purity. The characteristic peaks of UIO-66 and BiOI can be observed in the XRD spectrum of Bi / UiO-66 composite materials, and the corresponding 2θ angles of BiOI and UiO-66 can be found in the Bi / UiO-66 spectrum, which proves that the Bi / UiO-66 binary material is successfully composited. Due to the low BiOI content, the peak intensity is weak.

[0025] Example 3: Photocatalytic experiment The Bi / UiO-66 composite material provided by the present invention has strong photocatalytic performance for antibiotics, especially for quinolone antibiotics, tetracycline antibiotics, etc., which can achieve ideal photocatalytic adsorption and degradation effects. A photocatalytic degradation experiment was carried out with 100mL, 10mg / L of norfloxacin as the target pollutant. At room temperature, 20mg of different Bi / UiO-66 composite materials prepared in Example 1 were weighed respectively, and BiOI and UiO-66 were used as controls for photocatalytic degradation reaction. Prior to the dark reaction for 30min, the photocatalytic degradation was carried out for 60min under a xenon lamp with a wavelength of 400-750λm and 250w, and the photocatalytic performance of each reagent was measured every 5min. Figure 2 is a photocatalytic degradation curve of norfloxacin by BiOI monomer and different Bi / UiO-66 composite materials prepared in Example 1; Figure 2 It can be seen that compared with BiOI and UIO-66 monomers, the Bi / UiO-66 composite material provided by the present invention has a relatively ideal photocatalytic degradation ability for the quinolone antibiotic norfloxacin. The final removal rates of Bi / UiO-66=0.1:1, Bi / UiO-66=0.2:1, Bi / UiO-66=0.3:1, Bi / UiO-66=0.4:1, and Bi / UiO-66=0.5:1 are 97.03%, 91.01%, 89.21%, 87.57%, and 88.05%, respectively.

[0026] In order to explore the light absorption capacity of the above-mentioned different materials and their influence on catalytic performance, different materials were characterized by UV-Vis DRS. Figure 3The following are the UV diffuse reflectance images of the UiO-66 monomer and the series of Bi / UiO-66 composite materials prepared in Example 1. Figure 3 As shown, UIO-66 monomer and different Bi / UiO-66 composites have good light absorption performance in the ultraviolet light region of 200 ~350nm, among which UIO-66 and Bi / UIO-66=0.1:1 have similar light absorption intensities; Bi / UIO-66=0.2:1~Bi / UIO-66=0.5:1 have similar light absorption intensities, which are higher than the light absorption intensities of UIO-66 monomer and UIO-66 and Bi / UIO-66=0.1:1.

[0027] In order to study the photocatalytic mechanism of the composite material, 20 mg of Bi / UiO-66=0.1:1 photocatalyst was taken, and 10 mmoL / L isopropyl alcohol (IPA), 5 mmoL / L p-benzoquinone (BQ) and 10 mmoL / L sodium oxalate (SO) were selected as hydroxyl radicals (•OH), superoxide radicals (•O2) and photogenerated holes (h + ) was used as an active collector to degrade 10 mg / L of norfloxacin (NOR). Figure 4 This is the active capture photocatalytic degradation diagram of Bi / UIO-66=0.1:1. Figure 4 It can be seen that isopropyl alcohol (IPA) has a significant effect on the photocatalytic degradation effect, indicating that hydroxyl radicals (•OH) are the main active substances in the photocatalytic degradation of norfloxacin by the composite material.

[0028] Ion tolerance is an important indicator for the practical application of photocatalysts. In 100mL and 10mg / L norfloxacin solutions, the conditions of no sodium chloride, 5mg, 10mg, 20mg and 30mg sodium chloride were set respectively, and photocatalytic degradation was carried out using 20mgBi / UIO-66=0.1:1. Figure 5 The following are the degradation diagrams of Bi / UIO-66=0.1:1 with different ion concentrations; in the figure, (a) is the degradation curve and (b) is the degradation rate. Figure 5 As shown in the figure, the degradation rate curves are basically the same, and the removal rates are 89.73%, 90.59%, 87.64%, 91.23% and 88.02% respectively. k The values ​​are 0.0249min -1 , 0.02522 min -1 、0.02356min -1 , 0.02352 min -1 and 0.02639 min -1 . This indicates that 0.1:1 Bi / Uio-66 has excellent ion tolerance during the photocatalytic process.

[0029] 100 mL, 10 mg / L of norfloxacin was cyclically degraded in 20 minutes. Figure 6 is the cyclic degradation diagram of norfloxacin with Bi / UIO-66=0.1:1; Figure 6 It can be seen that with the increase of the number of cycles, the efficiency of norfloxacin degradation gradually decreased, but even in the fifth cycle, the degradation rate can still be maintained above 80%. This shows that the Bi / UiO-66 composite material has good photocatalytic stability and repeatability, and still has considerable treatment effect after multiple catalytic degradation. It has great commercial promotion value in practical application.

[0030] The effects of different mass concentrations (0.1 g / L, 0.2 g / L, 0.4 g / L and 0.6 g / L) of Bi / UIO-66=0.1:1 composite materials on the photocatalytic degradation performance of 10 mg / L NOR were studied. Figure 7 The following is the photocatalytic degradation diagram of Bi / UIO-66=0.1:1 with different mass concentrations; (a) is the degradation curve and (b) is the degradation rate. Figure 7 It can be seen that the adsorption rate of Bi / UIO-66=0.1:1 at mass concentrations of 0.1g / L, 0.2g / L, 0.4g / L and 0.6g / L gradually increased, and the final removal rates were 79.57%, 91.23%, 80.56% and 90.28% respectively. The first-order kinetic fitting formula was used to further study the photocatalytic efficiency of Bi / Uio-66 at different concentrations of 0.1:1; the reaction rate constants of 0.1g / L, 0.2g / L, 0.4g / L and 0.6 g / L k The values ​​are 0.01493min -1 、0.0249min -1 、0.01821min -1 and 0.02534 min -1 In comparison, when the concentration was 0.2 g / L, the photocatalytic degradation performance was best when Bi / UIO-66=0.1:1.

[0031] Example 4 Referring to the preparation method of the Bi / UiO-66 composite material in Example 1, the organic ligand terephthalic acid was adjusted to 0.1811g of 2-aminoterephthalic acid, and the regulator acetic acid was adjusted to 3.6mL HCl to obtain a homogeneous suspension D; the homogeneous suspension D was transferred to a 100mL polytetrafluoroethylene-lined stainless steel reactor, and the solution was cooled to room temperature after reacting at 100°C for 30h, and washed with ethanol and deionized water 3 times, and dried at 80°C for 12h to obtain a Bi / UiO-66 composite material, which was recorded as Bi / UiO-66-01. The photocatalytic experiment was carried out on it according to the method in Example 3, and the removal rate was about 95.35%.

[0032] Example 5 Referring to the preparation method of the Bi / UiO-66 composite material in Example 1, the organic ligand terephthalic acid was adjusted to 0.1861g of 2-hydroxyterephthalic acid, and the regulator acetic acid was adjusted to 3.6mL of trifluoroacetic acid to obtain a homogeneous suspension E; the homogeneous suspension E was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the solution was cooled to room temperature after reacting at 140°C for 12h, and washed with ethanol and deionized water for 5 times, and dried at 70°C for 14h to obtain a Bi / UiO-66 composite material, which was recorded as Bi / UiO-66-02. The photocatalytic experiment was carried out on it according to the method in Example 3, and the removal rate was about 93.62%.

[0033] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention.

Claims

1. A Bi / UiO-66 binary composite photocatalytic material, characterized in that: The preparation method is as follows: (1) Dissolve Bi(NO3)3·5H2O and KI in ethylene glycol, transfer to a stainless steel reactor lined with polytetrafluoroethylene after ultrasonic stirring, and cool the solution to room temperature after high temperature reaction, wash and dry to obtain BiOI; (2) ZrCl4, the organic ligand, and the BiOI prepared in step (1) are dissolved in a DMF solution and stirred evenly, a regulator is added, and ultrasonic stirring is performed to obtain a homogeneous suspension; the homogeneous suspension is transferred to a stainless steel reactor lined with polytetrafluoroethylene, reacted at high temperature, cooled to room temperature, washed, and dried to obtain a Bi / UiO-66 composite material.

2. The binary composite photocatalytic material according to claim 1, characterized in that: In step (1), the amounts of Bi(NO3)3·5H2O, KI, and ethylene glycol are 5 mmoL, 5 mmoL, and 40 mL, respectively.

3. The binary composite photocatalytic material according to claim 1, characterized in that: The temperature of the high temperature reaction in step (1) is 150-170° C., and the time of the high temperature reaction is 10-12 h.

4. The binary composite photocatalytic material according to claim 1, characterized in that: The mass ratio of Bi to UIO-66 in the Bi / UiO-66 composite material in step (2) is 0.1-0.5:

1.

5. The binary composite photocatalytic material according to claim 1, wherein the amount ratio of ZrCl4, organic ligand, BiOI and DMF in step (2) is 1 mmoL: 1 mmoL: 0.0467-0.2335 g: 50 mL.

6. The binary composite photocatalytic material according to claim 1, characterized in that: The molar ratio of the organic ligand to the regulator is 1:1; the regulator is selected from formic acid, acetic acid, trifluoroacetic acid, HCl, HF, and water; the organic ligand is selected from terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-bromoterephthalic acid, 2-nitroterephthalic acid, 1,2,4-benzenetricarboxylic acid, 2,5-diaminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dimercaptoterephthalic acid or 2,3,4,6-tetrafluoroterephthalic acid.

7. The binary composite photocatalytic material according to claim 1, characterized in that: The temperature of the high temperature reaction in step (2) is 100-140° C., and the time of the high temperature reaction is 12-30 hours.

8. The Bi / UiO-66 composite material prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the Bi / UiO-66 composite material according to claim 8 in the field of antibiotic adsorption in water.

10. The use according to claim 9, characterized in that: The antibiotics are one or more of quinolone antibiotics and tetracycline antibiotics.

Citation Information

Cited By

  • Composite metal organic layer material and preparation method thereof, and method and system for preparing medium-chain fatty acid

    CN120790236A

  • A composite metal-organic layer material and its preparation method, a method and system for preparing medium-chain fatty acids.

    CN120790236B